Genetic Modification of Limbal Stem Cells to Decrease Allogeneic Immune Responses - Valdivia, Emilio; Bertolin, Marina; Breda, Claudia; Carvalho Oliveira, Marco; Salz, Anna Katharina; Hofmann, Nicola; Börgel, Martin; Blasczyk, Rainer; Ferrari, Stefano; Figueiredo, Constanca (Frontiers in Immunology, 2021)
Limbal stem cell (LSC) transplantation is the only efficient treatment for patients affected by LSC deficiency (LSCD). Allogeneic LSC transplantation is one of the most successful alternative for patients with bilateral LSCD. Nevertheless, the high variability of the human leukocyte antigens (HLA) remains a relevant obstacle to long-term allogeneic graft survival. This study characterized the immunologic properties of LSCs and proposed a genetic engineering strategy to reduce the immunogenicity of LSCs and of their derivatives. Hence, LSC HLA expression was silenced using lentiviral vectors encoding for short hairpin (sh) RNAs targeting β2-microglobulin (β2M) or class II major histocompatibility complex transactivator (CIITA) to silence HLA class I and II respectively. Beside the constitutive expression of HLA class I, LSCs showed the capability to upregulate HLA class II expression under inflammatory conditions. Furthermore, LSCs demonstrated the capability to induce T-cell mediated immune responses. LSCs phenotypical and functional characteristics are not disturbed after genetic modification. However, HLA silenced LSC showed to prevent T cell activation, proliferation and cytotoxicity in comparison to HLA-expressing LSCs. Additionally, HLA-silenced LSCs were protected against antibody-mediated cellular-dependent cytotoxicity. Our data is a proof-of-concept of the feasibility to generate low immunogenic human LSCs without affecting their typical features. The use of low immunogenic LSCs may offer support for long-term survival of LSCs and their derivatives after allogeneic transplantation..